Field and farm size optimization of agricultural ecosystems : decision making at the local government level in intensively used agricultural lands in Germany - Eigner, Amanda E.; Justus Liebig University Giessen (My University, 2017)
The model approach combines agricultural land use decisions of farmers with economic principles of cost reductions, namely economies of size being a driver of structural change. In order to apply a political impact assessment of the new "CAP towards 2020" reform the concept of socio-ecological resilience is applied to a small municipality lying in one of the most intensively used agricultural area in Wetterau county in Hesse, Germany. The model (FOLAS) simulates farmers´ decisions at several scales. At the field scale it takes into account field sizes. Each farmer is represented by a certain consolidated cropping area on which field size and cropping decisions take place (the farm scale). Neighbouring farmers are linked together via land leases and landscape changes are simulated. Several farm types and sizes were differentiated. In an iterative process, short and long-term farming decisions were simulated using a combination of linear mixed integer and non-linear programming models that underlie certain spatial and temporal assumptions. The model results were visualized in a stylized rectangular form using GIS. Based on resulting maps, three different biodiversity indicators linked to landscape heterogeneity were applied. In addition, three different policy designs were tested: (1) CAP I, which is adapted to the new CAP towards 2020´ reform; (2) CAP II with a stricter CAP towards 2020´ reform; and (3) a nature-focused´ policy design with a completely different governmental payment structure based on incentive-based payments for environmental measures. Results showed that in the CAP I and II policy designs, biodiversity indicators had negative trends. The new CAP towards 2020´ reform seems to be ineffective in reaching the biodiversity targets of the EC within the case study. It accelerated structural change and led to a more homogeneous landscape due to fewer farms and bigger fields. In the nature-focused´ policy design structural change processes were slower since fewer farms closed down. It had significant positive impacts on chosen biodiversity indicators and seemed to be superior with respect to achieving the EC biodiversity targets. Due to incentive-based environmental measurements, many more semi-natural habitats in the form of flowering strips and fields have emerged. However, in order to compensate income losses of the nature-focused´ policy design, structural change seem to be required (although of lesser magnitude). In all policy designs, dairy farmers quit the agricultural sector, which led to a less diverse cropping pattern at the municipality level. Further, semi-natural habitats conglomerated in areas where already a larger amount of semi-natural habitats occurred. FOLAS captures a long time frame and is adapted to the local and spatial production conditions. This novel spatial approach lays an important cornerstone for the development of spatially and temporally explicit bio-economic models.

Der Modellansatz kombiniert landwirtschaftliche Landnutzungsentscheidungen mit ökonomischen Prinzipien der Kostensenkung: der Erhöhung von Skalenerträgen als ein Merkmal des landwirtschaftlichen Strukturwandels. Für ein kleines Untersuchungsgebiet, welches inmitten einer landwirtschaftlich intensiv genutzten Region (Wetterau, Hessen) liegt, wurde mit Hilfe des Konzepts der sozio-ökologischen Resilienz eine agrarpolitische Folgeabschätzung der Agrarreform von 2015 durchgeführt.Das Modell (FOLAS) simuliert landwirtschaftliche Entscheidungen auf mehreren Ebenen. Auf der kleinsträumlichen Ebene werden Schlaggrößen berücksichtigt. Dazu wird jedem Landwirt eine bestimmte arrondierte Fläche zugewiesen, auf der Schlag- und Landnutzungsentscheidungen modelliert werden. Benachbarte Betriebe sind über die Verpachtung von Flächen miteinander verknüpft um landschaftliche Veränderungen zu simulieren. Kurz- und langfristige Betriebsentscheidungen unterschiedlicher Betriebstypen und -größen werden mit Hilfe eines iterativen Prozesses unter Verwendung einer Kombination aus linearen gemischt ganzzahligen und nicht-linearen mathematischen Programmiermodellen unter bestimmten räumlichen und zeitlichen Annahmen simuliert. Die Ergebnisse werden mit einem geographischen Informationssystem in einer rechteckigen Form räumlich dargestellt. Auf der Grundlage der erstellten Karten werden drei Biodiversitätsindikatoren, die in Zusammenhang mit der Landschaftsheterogenität stehen, berechnet. Zudem werden drei verschiedene politische Szenarien modelliert: (1) CAP I, welches an die neue Agrarreform von 2015 angepasst ist, (2) CAP II mit strengeren Umweltauflagen und (3) das nature-focused Szenario, welches eine Umstrukturierung der staatlichen Zuwendungen auf Grundlage von anreizbasierten Zahlungen vorsieht. Die Ergebnisse zeigen, dass in CAP I und II alle Biodiversitätsindikatoren einen negativen Trend aufweisen. Die neue Agrarreform von 2015 scheint demnach innerhalb der Untersuchungsregion ineffizient hinsichtlich der Erreichung der von der Europäischen Kommunion gesetzten Biodiversitätsziele zu sein. Die neue Reform verstärkt den Strukturwandel und führt zu einer homogeneren Landschaft mit weniger Betrieben und größeren Schlägen. Im nature-focused Szenario ist der Strukturwandel langsamer (weniger Betriebsaufgaben). Es hat signifikante positive Auswirkungen auf ausgewählte Biodiversitätsindikatoren und scheint hinsichtlich der Erreichung der Biodiversitätsziele den beiden anderen Szenarien überlegen zu sein. Aufgrund von anreizbasierten Zahlungen konnte eine erhöhte Anzahl semi-natürlicher Habitate in Form von Blühflächen erreicht werden. Um jedoch die Einkommenseinbuße der Landwirte zu kompensieren, scheint ein moderater Strukturwandel notwendig zu sein. In allen Szenarien kam es zu Betriebsaufgaben aller Milchviehbetriebe, was zu einer Reduzierung der Anbauvielfalt auf der Gemeindeebene führt. Zudem kam es zu einer Aggregation von semi-natürlichen Habitaten.FOLAS deckt eine große Zeitspanne ab und ist an die örtlichen räumlichen Produktionsbedingungen angepasst. Dieser neue räumliche Ansatz stellt eine wichtige Grundlage zur Entwicklung von räumlich und zeitlich expliziten bio-ökonomischen Modelle dar.
Schlag- und Betriebsgrößenoptimierung von Agrarökosystemen : Entscheidungsfindung auf der Gemeindeebene in einem landwirtschaftlich intensiv genutzten Gebiet in Deutschland
Keywords: Landschaftshomogenität; Strukturwandel; räumlich explizit; Optimierungsmodell; Skalenerträge; landscape heterogeneity; structural change; spatially explicit; optimization model; economies of scale; ddc:630